Whole rethinking the science of nutrition - Campbell, T. Colin 1934- (BenBella Books, Inc., 2013)
"The China Study" revealed what we should eat and provided the powerful empirical support for this answer. "Whole" answers the question of why. Why does a whole-food, plant-based diet provide optimal nutrition? "Whole" demonstrates how far the scientific reductionism of the nutrition orthodoxy has gotten offtrack and reveals the elegant wonders of the true holistic workings of nutrition, from the cellular level to the operation of the entire organism.